2002
DOI: 10.1039/b202943j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel 1,3-bis(5-diarylaminothiophen-2-yl)isothianaphthenes

Abstract: We report the synthesis, electrochemical and optical properties of novel 1,3-bis(5-diarylaminothiophen-2-yl)isothianaphthenes obtained by palladium-catalysed amination of 1,3-bis(5-bromothiophen-2-yl)isothianaphthene with diarylamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Diphenylamine has been coupled with 2‐halothiophenes, in the presence of a palladium source (Pd(OAc) 2 26, 27 or [Pd 2 dba 3 ] {dba=dibenzylideneacetone}26) in conjunction with P t Bu 3 (36–78 % from 2‐bromothiophene2628), or by use of CuI‐mediated modified Ulmann conditions (40 % yield from 2‐iodothiophene) 29. Various other diarylamines including bis(4‐alkoxyphenyl)amines have been coupled with α,α′‐dibromooligothiophenes and with 1,3‐bis(5‐bromothien‐2‐yl)benzo[ c ]thiophene in moderate yields in the presence either of Pd(OAc) 2 /P t Bu 3 30 or of [Pd(dppf)Cl 2 ]/dppf {dppf=1,1′‐bis(diphenylphosphino)ferrocene}31 as catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Diphenylamine has been coupled with 2‐halothiophenes, in the presence of a palladium source (Pd(OAc) 2 26, 27 or [Pd 2 dba 3 ] {dba=dibenzylideneacetone}26) in conjunction with P t Bu 3 (36–78 % from 2‐bromothiophene2628), or by use of CuI‐mediated modified Ulmann conditions (40 % yield from 2‐iodothiophene) 29. Various other diarylamines including bis(4‐alkoxyphenyl)amines have been coupled with α,α′‐dibromooligothiophenes and with 1,3‐bis(5‐bromothien‐2‐yl)benzo[ c ]thiophene in moderate yields in the presence either of Pd(OAc) 2 /P t Bu 3 30 or of [Pd(dppf)Cl 2 ]/dppf {dppf=1,1′‐bis(diphenylphosphino)ferrocene}31 as catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The BMA-nT series has been modified to show electronic absorption in the visible wavelength region by the replacement of the thiophene unit with a isothianaphthene group. 165 A p-n heterojunction photovoltaic device consisting of a triarylphthalocyanine-based amorphous molecular material, PcArA (M: TiLO), as a p-type semiconductor and N,N9-dimethyl-3,4,9,10-perylenebis(dicarboximide) (MPCI) as an n-type semiconductor exhibited PV properties when irradiated with 400-600 nm light which MPCI absorbs. The action spectrum resembled the electronic absorption spectrum of MPCI.…”
Section: -4 Emitting Amorphous Molecular Materialsmentioning
confidence: 99%
“…7 It has been revealed that polybenzo [c]thiophenes possess unique optical properties originating from their narrow HOMO−LUMO energy gaps over the past few decades. 8 More recently, functionalized benzo [c]thiophene monomers were also synthesized aiming to their use in solar cells, 9 electroluminescence devices, 10 and so on. 11 A general method for benzo [c]thiophene synthesis is the ring closure of the corresponding ortho-dicarbonyl benzene derivatives by treating with Lawesson's reagent (Scheme 1a).…”
Section: ■ Introductionmentioning
confidence: 99%